The relationship between countermovement jump force-time characteristics and 2,000-m rowing ergometer performance - Joseph M. DeLeo; Joseph M. DeLeo; Alex Wolf; Nicolas M. Philipp; Kathryn E. Ackerman; Andrew C. Fry (Frontiers in Sports and Active Living)
BackgroundRowing is a strength-endurance sport. The Olympic race distance of 2,000-m (2k) requires extensive aerobic and anaerobic energy system contributions, along with sustained high force output.Aim(s)The primary aim of this study was to evaluate the relationship between rowing ergometer (erg) performance and the force-time curve characteristics of a counter-movement jump (CMJ), and to determine if rowing-related low back pain (LBP) affected these relationships.MethodsAthletes completed a 2k time trial at the 2023 USRowing Atlantic City Indoor National Championships as well as a CMJ on force plates. Data from the 2k (n = 27) time trial was analyzed to determine significant relationships between CMJ force-time characteristics and 2k rowing ergometer performance. Partial correlations were used to determine the effects rowing-related LBP has on the relationship between 2k erg and CMJ force-time curve characteristics.ResultsPositive Take-off Impulse had the strongest correlation with 2k erg performance (r = 0.71, p < 0.001). Jump height was not significantly related to 2k erg performance (r = −0.13, p = 0.518). Current LBP changed the relationship for Concentric Mean Force (r = 0.74, p < 0.001).ConclusionPositive Take-off Impulse has a strong, positive relationship to 2k erg performance. CMJ variables related to impulse and force should be monitored longitudinally to see if changes in these variables coincide with improved 2k rowing erg performance and the assessment of neuromuscular fatigue. Coaches can utilize these findings to individualize strength and power training for potential 2k erg performance improvements.